The modern management of macroprolactinomas. - Grossman, A (1991)
Macroprolactinomas will usually shrink with dopamine agonist therapy, often to within the pituitary fossa; definitive treatment with radiotherapy can then achieve eventual normalization of serum prolactin in the majority of patients. Persistent suprasellar extensions, even when relatively large, can usually be successfully decompressed by the transsphenoidal route. Stalk compression can also give rise to hyperprolactinemia that will normalize with bromocriptine, but tumors causing it will rarely, if ever, show significant shrinkage in response to the drug.